Emergence of dalbavancin non-susceptible, vancomycin-intermediate Staphylococcus aureus (VISA) after treatment of MRSA central line-associated bloodstream infection with a dalbavancin- and vancomycin-containing regimen. (April 2018) - Werth, B.J.; Jain, R.; Hahn, A.; Cummings, L.; Weaver, T.; Waalkes, A.; Sengupta, D.; Salipante, S.J.; Rakita, R.M.; Butler-Wu, S.M.
Abstract: Objectives: Dalbavancin is a long-acting lipoglycopeptide with activity against gram-positives, including methicillin-resistant Staphylococcus aureus (MRSA). The potential for lipoglycopeptides, with half-lives greater than 1 week, to select for resistance is unknown. Here we explore a case of MRSA central line-associated bloodstream infection in which dalbavancin and vancomycin non-susceptibility emerged in a urine isolate collected after the patient was treated with vancomycin and dalbavancin sequentially. Methods: Isolates from blood and urine underwent susceptibility testing, and whole genome sequencing (WGS). The blood isolate was subjected to successive passage in vitro in the presence of escalating dalbavancin concentrations and the emergent isolate was subjected to repeat susceptibility testing and WGS. Results: The blood isolate was fully susceptible to vancomycin; however, MICs of the urine isolate to dalbavancin, vancomycin, telavancin, and daptomycin were at least fourfold higher than the blood-derived strain. Both strains were indistinguishable by spa and variable number tandem repeat (VNTR) typing, and WGS revealed only seven variants, indicating clonality. Four variants affected genes, including a 3bp in-frame deletion in yvqF, a gene which has been implicated in glycopeptide resistance. Vancomycin and dalbavancin non-susceptibility emerged in the blood isolate after successive passage in vitro in the presence of dalbavancin, and WGS identified a single non-synonymous variant in yvqF . Conclusions: This is the first case in which VISA has emerged in the context of a dalbavancin-containing regimen. The selection for cross-resistance to vancomycin in vitro by dalbavancin exposure alone is troubling. Clinicians should be aware of the possibility for emergence of dalbavancin non-susceptibility and glycopeptide cross-resistance arising following therapy.